Status of Intestinal Schistosomiasis in Buffaloes and Cattle in Rajshahi, Bangladesh - Rashid, Md Mamunur; Uddin, Md Zamal; Hossain, Md Zakir; Sharma, Bikash; Raihan, Jafor; Ali, Md Sumon; Nahar, Lovely; Moni, Mst Ishrat Zerin; Rahman, Moizur (Research in Agriculture Livestock and Fisheries, 2022)
Schistosoma infection causes serious health impediment in livestock with poor productive and reproductive performances. This study was carried out to know the status of Schistosoma infection in buffaloes and cattle in Rajshahi, Bangladesh. The adult schistosomes were collected from mesenteries of buffaloes and cattle of Rajshahi. Out of 240 mesenteries (120 from each species) examined, 113 (47.08%) were found infected. The infection rate in buffaloes and cattle were 54.16% and 40%, respectively. Female buffalo and cattle (57.69% and 46%) were more prone to the infection than male (51.47% and 36.71%) although the differences were not statistically significant. Significant variations (p<0.05) were observed in infection rate in different season. The highest infection rate was observed in rainy season (85% and 65%) followed by summer (52.5% and 40%) and winter (25% and 15%) in both the animals. Intensity of the infection greatly varied. Mostly, half of the infected animal (55% buffalo and 46% cattle) showed moderate infection intensity (51 to 100 parasites/animal). High degree of infection (>100 parasites/animal) was found in 25% and 33% infected buffalo and cattle, respectively. Two species of intestinal schistosomes (S. indicum and S. spindale) were identified microscopically by observing egg of female parasites. S. indicum was present in all the infected mesenteries whereas only 29% buffaloes and 35% cattle samples contained S. spindale. The study determined the current scenario of intestinal schistosome infection in buffaloes and cattle of Rajshahi. The findings might be helpful to develop effective strategic plan to overcome the harmful effects of schistosomes in livestock of Bangladesh. Vol. 9, No. 2, August 2022: 201-211